DESIGNING COMPUTER-BASED EXERCISES USING WEBLOG, HOT POTATOES SOFTWARE AND SKYPE MESSENGERS IN CREATING IDEAS TO FACILITATE INDEPENDENCE LEARNING OF READING COMPREHENSION - Lusy Tunik Muharlisiani; Anang Kukuh; Siti Azizah (Eltin Journal : Journal of English Language Teaching in Indonesia, 2018)
The design-based research methodology explicates how design not only allowed more effective student representation and sharing of the different levels of knowledge required for abstraction to occur, but also enabled better teacher assessment and, hence, remediation also provides detailed guidance on creating interactive content (from the application of learning strategies and media to courseware development). On the basis of the emerging findings of the study a set of principles for designing web-conferencing (or other online) environments to support creative design learning is proposed. This mainly addresses trainers and instructional designers who aim to create learning projects that really match learners’ needs, was considered appropriate and suitable for the students to develop their reading comprehension. This interactive and interesting design would increase the students’ motivation to learn reading comprehension in fun environment. It is expected that they could change their habit of the learning by accessing the exercises regularly as the mediaKeywords: Weblog, Hot Potatoes Sofware, Skype Messengers, and Reading Comprehension